The Added Value of Professional Development Programs: Insights from a Case Study - Wintersberg, Lisa; Trikoili, Anna; Abdullah, Razin; Pittich, Daniel (Social Education Research, 2025)
The effectiveness of lifelong learning programs designed for professionals relies on the transfer of the learnings to their workplaces. While the programs' quality is constantly evaluated, measuring whether the transfer takes place remains a significant challenge. With this study, we attempt to provide a triangulated measuring approach. We aim first to explore the factors that enhance or hinder learning transfer and second to describe instances when professionals applied newly acquired knowledge in their daily work life. In this mixed-methods study, twelve participants from a lifelong learning master's program completed the Learning Transfer System Inventory (LTSI) to identify factors influencing learning transfer. To triangulate the data, eight of them also provided open-ended reflections on specific transfer experiences, which were used as qualitative data. We found that psychological factors like motivation and peer support are strongly linked to learning transfer, while participants also felt that the program's content should be more relevant to their work. Moreover, our findings suggest that meeting the learning goals is not the key indicator of a lifelong learning program's success. Rather, the quality of these programs is defined by the extent of the participants' professional development. To approach the challenge of measuring transfer effectively and to achieve an in-depth evaluation, we call upon including a holistic approach combining qualitative and quantitative measurement methods as well as input from different stakeholders, instead of purely relying on self-report data.